Negation Form in Tidung Language - Romadhan, Achmad Dicky (Journal Corner of Education, Linguistics, and Literature, 2024)
In daily communication, Tidung speakers often utilize negation forms for rejection, cancellation, and negation. This linguistic phenomenon is very interesting to study. This paper aims to describe the form of negation in Tidung language and its usage. This study of negation in Tidung language uses descriptive method. The source of data comes from written and spoken discourse, especially those that contain the use of negation forms. The data were collected using reading, note-taking, and interview techniques. The data analysis technique used is qualitative descriptive analysis technique. In this paper, several forms of negation in Tidung language are found, including negation of kamad, ando, sama and kamad sino. These forms of negation have different functions and meanings. The use of negation in Tidung language can occur in parts of sentences contained in compound sentences and in the whole sentence contained in single sentences. Judging from the rigidity of the location, the five negations are very strong because the position of the negation cannot be moved to the right of the predicate function or to the left of the subject and object functions.